Acquired hemophilia A: a review of recent data and new therapeutic options. Issue 9 (21st October 2017) - Franchini, Massimo; Vaglio, Stefania; Marano, Giuseppe; Mengoli, Carlo; Gentili, Sara; Pupella, Simonetta; Liumbruno, Giancarlo Maria
ABSTRACT: Objectives: Acquired hemophilia A (AHA) is a rare, but potentially life-threatening, bleeding disorder caused by an autoantibody against factor VIII that interferes with its coagulant function. Methods: We performed a narrative review focusing on the diagnostic aspects of AHA and on the current treatment strategies with particular regard to new data and therapeutic developments. Results: The management of this severe hemorrhagic disorder is based on the control of bleeding with the use of bypassing agents and on the utilization of a variety of immunosuppressant agents with the goal of eliminating the autoantibody permanently. Conclusion: The optimal management of AHA should be multidisciplinary and requires a close collaboration between physicians from various specialties.